Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Record Keeping for Beef Quality Assurance - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS, 2006)
AN172 includes pages 37-42 of the Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. It covers record keeping practices necessary for Beef Quality Assurance. It includes examples of forms and a table with record keeping requirements of relevant state and federal laws. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006. Reviewed November 2009.